Integrative effects of transcutaneous auricular vagus nerve stimulation on esophageal motility and pharyngeal symptoms via vagal mechanisms in patients with laryngopharyngeal reflux disease - Huang, Yizhou; Liu, Jie; Lv, Chaolan; Sun, Chenyu; Meng, Muzi; Lowe, Scott; Yu, Yue (Frontiers in Neuroscience, 2024)
Abstract Background & Aim: Laryngopharyngeal reflux disease (LPRD) is primarily characterized by discomfort in the pharynx and has limited treatment options. This research aimed to assess the efficacy of transcutaneous auricular vagus nerve stimulation (tVNS) in patients with LPRD and delve into the potential underlying mechanisms. Methods: A total of forty-four participants, diagnosed with LPRD were divided into two groups randomly. Twice-daily stimulation was delivered for two weeks for patients in experimental group, with stimulation ranging from 1.0mA to 1.5mA (n=22), while the control group underwent sham tVNS (n=22) with the same stimulation parameters and different anatomical location. The severity of symptoms and levels of anxiety and depression were monitored using questionnaires. High-resolution esophageal manometry data were collected, and the patients' autonomic function was assessed through heart rate variability analysis. Results: There was a positive correlation between reflux symptom index (RSI) scores and low frequency/high frequency (LF/HF) ratio (r=0.619; P < 0.001), Hamilton anxiety scale (HAMA) scores (r=0.623; P < 0.001), and Hamilton depression scale (HAMD) scores (r=0.593; P < 0.001). Compared to the pre-tVNS phase, RSI (P < 0.001), HAMA (P < 0.001), and HAMD (P < 0.001) scores were significantly reduced after two weeks of treatment. Additionally, the resting pressure of the upper esophageal sphincter (UESP) (P < 0.05) and lower esophageal sphincter (LESP) (P < 0.05) showed significant enhancement. Notably, tVNS led to an increase in root mean square of successive differences (RMSSD) (P < 0.05) and high frequency (HF) (P < 0.05) within heart rate variability compared to the pre-treatment baseline. Compared to the control group, RSI (P < 0.001), HAMA (P < 0.001), and HAMD (P < 0.001) scores in tVNS group were significantly lower at the end of treatment. Similarly, the resting pressure of UESP (P < 0.05) and LESP (P < 0.05) in tVNS group were significantly higher than that of control group. Conclusions: This study demonstrated that tVNS as a therapeutic approach is effective in alleviating LPRD symptoms. Furthermore, it suggests that improvements in esophageal motility could be associated with vagus nerve-dependent mechanisms.